Penerapan Strategi Integrated Marketing Communication Adhiwangsa Hotel and Convention Solo pada Event So Kiss Me 2024 - Traberaldi Rafa Otniel; Rahmat Wisudawanto; Esfandani Peni Indreswari (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
In addition to personal selling, Adhiwangsa Hotel and Convention Solo also utilized other IMC tools such as direct marketing, public relations, and digital marketing to maximize the effectiveness of their promotional efforts for the "So Kiss Me 2024" event. The hotel leveraged its existing customer database to send personalized invitations and promotions through WhatsApp, which proved to be an effective channel for engaging with customers directly. Social media platforms were also used to create awareness and drive attendance, with consistent messaging across all channels to maintain a unified brand voice. Furthermore, the hotel emphasized the importance of building strong relationships with its customers by maintaining regular communication. This strategy helped foster trust and loyalty, as customers felt valued and personally attended to. The event was promoted not only through traditional marketing tools but also through word-of-mouth, leveraging employees' personal networks to spread the message. The study also highlights the role of digital marketing tools in enhancing the reach of the hotel's communication efforts. By utilizing platforms like Instagram, Facebook, and WhatsApp, Adhiwangsa Hotel was able to reach a broader audience, particularly among younger consumers who are more active on social media. These platforms allowed for real-time updates, engagement, and interaction with potential customers, making the event more dynamic and accessible. Overall, the success of the "So Kiss Me" event can be attributed to the hotel's effective use of integrated marketing communications, where personal selling played a significant role in delivering a more personalized and direct message to potential customers. This case study illustrates the importance of adopting a multi-channel communication strategy to effectively engage target audiences and achieve marketing objectives.